Achilles heel of environmental risk from recycling of sludge to soil as amendment: A summary in recent ten years (2007–2016). (October 2016) - Liu, Hong-tao
Highlights: The risk posed by organic contaminants and pharmaceuticals from sludge amendment decrease over time. Salinity derived from sludge resulted in physiological damage to plants or seedling rather than potential risk to human health. Most severe risk posed by recycling of sludge to soil comes from heavy metal, particularly more mobile one (such as Cd). Long term and periodic monitoring to change and determination of limit on sludge recycling dose and frequency are needed. Abstract: Recycling sludge as a soil amendment has both positive and negative effects because of its enrichment in both nutrients and contaminants. So far, the negative effect has to be extensively investigated that the severities of different types of contaminants also remain unclear. The environmental behavior and risk of organic contaminant and pharmaceuticals, heavy metal and salt as well as pathogenic microorganisms brought by sludge amendment are summarized and discussed here. Organic contaminants and pharmaceuticals are typically found at low concentrations in sludge, the risks from sludge-amended soil decrease over time owing to its biodegradability. On the other hand, application of sludge generally increases soil salinity, which may cause physiological damage to plants grown in sludge-amended soil. In some extent, this negative effect can be alleviated by means of dilution; however, greater attention should be paid to long term increasing possible risk of eutrophication. Heavy metal (particularly of mobile heavy metals, such as Cd) with high concentrations in sludge and soil receiving considerable sludge can cause its incremental abundance in soil and crop contamination, further posing risks to humans, but most cases showed that there remained not excessive in heavy metal caused by sludge amendment. It is worth noting that increasing soil organic matter content may reduce transfer of heavy metal from soil to crops, but not restrict its uptake by crops at all. Combined literature together, it is summarized that heavy metal becomes a relatively severe bottleneck in recycling of sludge as soil amendment due to its non-biodegradability and potential damage to health by adventuring contamination from agricultural products. Particular attention should therefore be paid to long term monitoring the change of heavy metals concentration in sludge amended soil.